A CONCEPTUAL FRAMEWORK: FORENSIC ACCOUNTING AND CORPORATE GOVERNANCE MATURITY - Ali Rehman; Fathyah Hashim (International Journal of Accounting, Finance and Business, 2020)
Corporate governance maturity can be achieved when fraud within the organizationsare mitigated and controlled. These frauds and related activities have created the expectationgap and means to fulfill this gap is the evaluation of mature corporate governance and inclusionof forensic accounting as a system of governance management. This paper concentratestowards integrating related literature and empirical research to broaden the proposedcapacities of forensic accounting on corporate governance maturity specifically for the publiclisted companies. This paper will identify the two major roles of forensic accounting namelypreventive and detective roles. This paper also suggests that fraud risk assessment poses amediating role between forensic accounting and corporate governance maturity by linkingagency theory, fraud triangle theory, and path dependence theory. This paper recommends andstresses a promising proposition for future research and will also assist regulators andorganizations to formulate or update their codes and policies.